The complex interplay between gastrointestinal and psychiatric symptoms in irritable bowel syndrome: A longitudinal assessment. Issue 4 (27th July 2018) - Stasi, Cristina; Caserta, Anna; Nisita, Cristiana; Cortopassi, Sonia; Fani, Bernardo; Salvadori, Stefano; Pancetti, Andrea; Bertani, Lorenzo; Gambaccini, Dario; de Bortoli, Nicola; Dell'Osso, Liliana; Blandizzi, Corrado; et al.
Abstract: Aims: The aims of this study were to better define the relationship between irritable bowel syndrome (IBS) and psychiatric disorders and to examine the efficacy of paroxetine in the treatment of IBS patients. Methods: One hundred fifty subjects with diagnosis of IBS (Roma III criteria) and relative sub‐classification (constipated, diarrhea, and mixed) were assessed for psychopathological features and gastrointestinal symptoms using IBS Symptom Severity Score and were consecutively enrolled . Fifty patients assumed paroxetine for 16 weeks and were longitudinally evaluated. Results: The entire sample had a moderate/severe gastrointestinal symptomatology (IBS‐SSS 285.1 ± 98.6). The IBS subtypes were diarrhea (47.3%), constipated (32%), and mixed (20.7%). Panic disorder was found in 17.4% and major depressive episode in 14.7%. More than 50% of the patients showed "psychopathological features." This group showed more severe gastrointestinal symptoms and worse quality of life than the group without any psychiatric comorbidity (44%). Psychiatric patients also showed a significant impairment of physical state, subjective feeling of well‐being, and leisure activities when compared with no psychiatric patients. When the IBS‐SSS > 300 group was subgrouped in psychiatric (67.2%) and no psychiatric (32.8%), we found significant differences in all clinician‐administered and self‐reported scales with more severe psychopathological features in psychiatric group ( P  < 0.01). Among the patients treated with paroxetine, 34 (68%) completed the longitudinal evaluation showing a significant improvement of both psychiatric and gastrointestinal symptoms. Conclusions: This study confirms a high presence of psychiatric comorbidities, emphasizing the need for psychiatric screening in all patients with IBS; moreover, the longitudinal evaluation of patients treated with paroxetine showed a significant improvement of both psychiatric and gastrointestinal symptoms.